Correlation Between APTT and Anti-Tuberculosis Therapy Stages at Cempaka Health Center - Thuraidah, Anny; Oktiyani, Neni; Nurlailah, Nurlailah; Kustiningsih, Yayuk; Meilinda, Intan (Baiman Bauntung Batuah Center, 2025)
Tuberculosis (TB) is an infectious disease that is still a global health problem. TB treatment with anti-tuberculosis drugs can affect the hemostasis system, one of which is through changes in activated partial thromboplastin time (APTT). However, the relationship between APTT values ??and the phase of TB therapy is still not fully understood. This study aims to analyze the relationship between APTT values ??and the phase of TB therapy and patient characteristics, including age and gender. This study used a cross-sectional design with an accidental sampling technique involving 30 pulmonary TB patients undergoing anti-tuberculosis drug therapy at the Cempaka Health Center. APTT examination was performed using an automatic method with a normal value of 25–43 seconds. Statistical analysis used the Pearson correlation test for normally distributed data and the Spearman test for non-normally distributed data. The results showed that 63% of patients had normal APTT values ??(26.0–41.2 seconds; average 32.7 seconds), while 37% of patients experienced prolonged APTT (44.8–49.7 seconds; average 47.6 seconds). There was no significant relationship between APTT values ??and the TB therapy phase (p=0.165), age (p=0.249), and gender (p=0.630). There was no significant relationship between APTT values ??and TB therapy phase, age, and gender. However, these results indicate that some patients experience changes in the hemostasis system during TB therapy. This study suggests that monitoring APTT in TB patients undergoing anti-tuberculosis drug therapy is still needed to anticipate potential coagulation disorders. Further research with a larger sample size and control of nutritional factors and patient inflammation status is recommended to obtain a more comprehensive understanding of the effects of TB therapy on the hemostasis system.